English Teachers’ Questions in A Vietnamese High School Reading Classroom - Phuong, Yen Hoang; Nguyen, Lam Giang Thi (JEELS (Journal of English Education and Linguistics Studies), 2017)
Recently, developing students’ thinking, especially critical thinking (CT), has become a hot issue. Critical thinking has been claimed to have an important impact on learners’ reading comprehension because it can help them analyze, evaluate, construct their thinking, solving problems and reasoning (Ennis, 1989). However, the extent that teachers’ classroom activities contribute to developing students’ critical thinking has rarely been researched. The current case study was conducted with six EFL high school teachers and 10 reading lessons in Vietnam to explore the teachers’ use of questions and to analyze if these questions could facilitate the students’ critical thinking. Classroom observations and the cognitive domain of Bloom’s taxonomy were adapted as the research instruments. The study results reveal common types of questions are often used by high school teachers in their reading lessons. Suggestions are made on types of questions that teachers should function more in their class in order to enhance students’ critical thinking.